2003
DOI: 10.1093/jat/27.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of DRI® Methamphetamine, DRI Ecstasy, Abuscreen® ONLINE Amphetamine, and a Modified Abuscreen ONLINE Amphetamine Screening Immunoassays for the Detection of Amphetamine (AMP), Methamphetamine (MTH), 3,4-Methylenedioxyamphetamine (MDA) and 3,4-Methylenedioxymethamphetamine (MDMA) in Human Urine*

Abstract: The performances of four immunoassays (DRI amphetamines, DRI ecstasy, Abuscreen ONLINE amphetamines, and a modified Abuscreen ONLINE amphetamines) were evaluated for control failure rates, sensitivity, and specificity for amphetamine (AMP), methamphetamine (MTH), 3,4-methylenedioxyamphetamine (MDA), and 3,4-methylenedioxymethamphetamine (MDMA). The two DRI reagents and the ONLINE reagents were run according to manufacturer specifications using a Roche Hitachi Modular DDP system. The modified ONLINE reagent was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Studies showed cross-reactivity for the amphetamine immunoassay tests with endogenous amines or other amphetamine-like substances, e.g. ephedrine [4][5][6][7][8]. Lowering the limits for amphetamine and designer amphetamines to 50 ng/ml as done so in the updated version of the assessment criteria for driving ability was seen as a huge challenge for immunological tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed cross-reactivity for the amphetamine immunoassay tests with endogenous amines or other amphetamine-like substances, e.g. ephedrine [4][5][6][7][8]. Lowering the limits for amphetamine and designer amphetamines to 50 ng/ml as done so in the updated version of the assessment criteria for driving ability was seen as a huge challenge for immunological tests.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity between amphetamine tests and endogenous substances or drugs is a well-known problem [4][5][6][7][8]. There has even been discussion if immunoassay is an appropriate method in general related to the new requirements.…”
Section: Introductionmentioning
confidence: 99%
“…[23,55,56] Although the data presented represents a limited number of samples, DART-MS analysis has been employed for other more diversified compounds, with broadly similar results. [23,55,56] Although the data presented represents a limited number of samples, DART-MS analysis has been employed for other more diversified compounds, with broadly similar results.…”
Section: Current Limitations and Future Directionmentioning
confidence: 94%
“…Ultimately, preliminary testing methods are evaluated on their ease of use, cost, throughput, and numerous performance characteristics, such as limits of detection cut-offs and specificity/ cross-reactivity. [23,55,56] Although the data presented represents a limited number of samples, DART-MS analysis has been employed for other more diversified compounds, with broadly similar results. While these data represent an interesting alternative method for urine screening, numerous factors would affect such testing and would need to be studied in detail and validated before adoption of such as technique, including the ionization potential of the analyte and how the concentration of matrix components could affect DART ionization.…”
Section: Current Limitations and Future Directionmentioning
confidence: 94%
“…Immunoassay testing is quick and economical, but susceptible to cross-reactivity with compounds structurally similar to the target compound 16-19. For this reason, the identities of compounds triggering positive immunoassay results must be confirmed by a more specific technique, most often gas chromatography/mass spectrometry (GC/MS) or liquid chromatography/mass spectrometry (LC/MS).…”
mentioning
confidence: 99%